Mixing Social Into Social Media: On-Line Networking Is Transforming the Way of Business All Over the Globe - Adriana Manolica (CES Working Papers, 2011)
In last three years, we are witnessing an explosion on social media scene: more and more actors, spectacular growth. So, the social media phenomena cannot be ignored and it is global. Now, in 2011, Facebook is bigger than ever - the most visited site on the Internet. The popularity of social networks like Facebook, Twitter and YouTube, together with the growth of social technologies like blogs and wikis, presents a huge opportunity for marketers. This paper aims to present some facts about social-media users and about its incidence in Romania.
Keywords: J11; M31; 330; social-media; network Romania